The Maintenance of iCAP 6300 Inductively Coupled Plasma-Atomic Emission Spectrometrer - ZHAO Qing-ling; LI Qing-cai (Yankuang ceshi, 2014)
Inductively Coupled Plasma-Atomic Emission Spectrometer (ICP-AES) has played an important role in the detection of inorganic elements. After a period of usage, it was found that the solenoid valve for gas flow control shifted mechanically, and led to adversely impacting on the sampling system and data analysis. Frequent usage in continuous periods also caused attrition of the mechanic stopper and decreased the sensitivity of the instrument. The inductively coupled plasma was hard to ignite after a long period, however, the sample system and Ar concentration was normal when the instrument was checked. After careful analysis, the copper wire at the end of the igniting head was found to be rusted under the washout of high temperature tail gas. Therefore, the setup of a proper specification for ICP-AES operation is of great significance. Based on the practical experience in the operation of the iCAP 6300 instrument, a series of operations are described here to optimize the maintenance and improve the reliability of the instrument. The operations include calibrating gas flow using Manufacturing and Service software, and using C 193.091 nm spectrum for baseline calibration to CID detection. Moreover, the specification for maintenance of the igniting head, analysis database and de-ashing system is also illustrated, which is beneficial to improving the performance and utilization ratio of the equipment.